Antigen-independent Induction of Histamine Synthesis by Immunoglobulin E in Mouse Bone Marrow–derived Mast Cells - Tanaka, Satoshi (The Rockefeller University Press, 2002)
Immunoglobulin (Ig)E-mediated activation of mast cells has long been thought to occur only when FcεRI receptor-bound IgE is cross-linked via multivalent antigens. However, recent studies have raised the possibility that mast cells may be activated by the binding of IgE to the FcεRI receptor in the absence of antigen. Here we demonstrate that IgE binding without antigen induces the expression of histidine decarboxylase (HDC) in mouse interleukin (IL)-3–dependent bone marrow–derived mast cells (BMMCs). The induction of HDC by the binding of IgE was found to require an influx of extracellular calcium ions, which was attenuated by pretreatment with U73122, a phospholipase C inhibitor. Furthermore, the increase in HDC activity upon sensitization with IgE was completely suppressed by pretreatment of BMMCs with protein kinase C inhibitors, such as H7, staurosporine, and Gö6976. In addition, immediate activation of the tyrosine kinase Lyn was not detectable upon treatment with IgE. These results suggest that the binding of IgE to its receptor in the absence of antigen results in de novo synthesis of HDC in BMMCs through a signaling pathway distinct to that operating during antigen-stimulated FcεRI activation.